2019
DOI: 10.1089/neu.2018.6071
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Stress Symptoms after Pediatric Injury: Relation to Pre-Frontal Limbic Circuitry

Abstract: Pre-frontal limbic circuitry is vulnerable to effects of stress and injury. We examined microstructure of pre-frontal limbic circuitry after traumatic brain injury (TBI) or extracranial injury (EI) and its relation to post-traumatic stress symptoms (PTSS). Participants aged 8 to 15 years who sustained mild to severe TBI (n = 53) or EI (n = 26) in motor vehicle incidents were compared with healthy children (n = 38) in a prospective longitudinal study. At the seven-week follow-up, diffusion tensor imaging was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 94 publications
0
15
0
Order By: Relevance
“…This disparity could also point to long-term impacts of injury that are not restricted to TBI. Hospitalization, psychological trauma from the injury event, and biological responses associated with secondary injury (such as inflammation) could all contribute to alterations in brain structure and function even when the brain itself is not directly injured (McDonald et al , 2016;Sheeler, 2016;Yang et al , 2016;Nicholson et al , 2018;Ewing-Cobbs et al , 2019) .…”
Section: Discussionmentioning
confidence: 99%
“…This disparity could also point to long-term impacts of injury that are not restricted to TBI. Hospitalization, psychological trauma from the injury event, and biological responses associated with secondary injury (such as inflammation) could all contribute to alterations in brain structure and function even when the brain itself is not directly injured (McDonald et al , 2016;Sheeler, 2016;Yang et al , 2016;Nicholson et al , 2018;Ewing-Cobbs et al , 2019) .…”
Section: Discussionmentioning
confidence: 99%
“…However, findings have varied widely across studies. For example, both higher and lower fractional anisotropy (FA) have been reported in post-acute pediatric mild TBI (Babcock et al., 2015; Beek et al., 2015; Chu et al., 2010; Ewing-Cobbs et al., 2019; Mac Donald et al., 2019; Mayer et al., 2018; Murdaugh et al., 2018; Mustafi et al., 2018; Schmidt et al., 2018; Wilde et al., 2008), although a recent meta-analysis of mild TBI in children and adults suggested that FA is generally increased post-acutely but reduced in chronic injury phases (Eierud et al., 2014). Generally, mean diffusivity (MD) is reduced in children with mild TBI up to 6 months post-injury relative to controls (Babcock et al., 2015; Chu et al., 2010; Wilde et al., 2008), although differences have not been reported in all studies of chronic time periods (Bartnik-Olson et al., 2014; Königs et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, mean diffusivity (MD) is reduced in children with mild TBI up to 6 months post-injury relative to controls (Babcock et al., 2015; Chu et al., 2010; Wilde et al., 2008), although differences have not been reported in all studies of chronic time periods (Bartnik-Olson et al., 2014; Königs et al., 2018). Alterations of white matter microstructure have been reported in many regions, including the corpus callosum, cortico-spinal tract, thalamic radiations, superior longitudinal fasciculus, and frontal white matter (Babcock et al., 2015; Beek et al., 2015; Chu et al., 2010; Ewing-Cobbs et al., 2019; Königs et al., 2018; Mac Donald et al., 2019; Mayer et al., 2018; Murdaugh et al., 2018; Mustafi et al., 2018; Schmidt et al., 2018; Wilde et al., 2008). These subcortical white matter tracts have shown the greatest strain and parenchymal deformation in association with mild TBI (Okamoto et al., 2019; Wu et al., 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations